A Study Of The Skeletal Morphology Of The Indıvıduals Wıth Normal Occlusıon - Mirzen Arat; Dilek Erdem; Hakan Gögen (Galenos Yayinevi, 1992)
In this study facial morphology was evaluated in sagittal and vertical direction simultaneously. The samples consist of 50 males and 50 females having normal occlusion. The individuals were classified in sagittal and vertical direction according to ANB angle and Jarabak ratio. The distribution of the samples according to the sexes and facial skeletal pattern were analyzed statistically and some fundamental measurements have been compared in skeletal groups and sexes. According to the results of this study, the sagittal and vertical skeletal pattern of the face was found to be independent. Besides, anterior and posterior facial heights and Jarabak ratio were similar in sagittal skeletal groups but the measurements used in sagittal and vertical directions were different in vertically classified groups. The results of this study also bears some suspicion about the reliability of ANB angle.